Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan yang Dimediasi oleh Kepuasan Pelanggan pada Sales Person Dealer Honda Studi WOM Cabang Jatibarang - Rafsanzani, Mahdy Ardy; Saparso, Saparso; Teecoalu, Melitina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
WOM Finance is one of the multi-finance companies in Indonesia whose growth continues to increase. To be able to survive in the increasing competition in the field of financing services, Wom Finance continues to improve service quality which is expected to provide satisfaction value for customers and impact on customer loyalty to continue using financing services from Wom Finance. The purpose of this study was to determine and analyze the effect of service quality variables on customer loyalty mediated by customer satisfaction with a focus study on sales persons at Honda dealers in collaboration with the Jatibarang branch of Wom Finance. The number of respondents in this study were 73 respondents. The analysis technique used in this study is Path Analysis. The results of the analysis show that service quality has a positive effect on customer satisfaction and customer loyalty, customer satisfaction has a positive effect on customer loyalty but is not proven to have a positive effect on mediation relationships. The results of this study are expected to be a reference for Wom Finance and for companies in similar fields so that they are able to maintain and always improve service quality so that it has an impact on customer satisfaction and loyalty.â€